Effect of different WC particle shapes on laser-exposed microstructures during the directed energy deposition. (1st January 2022) - Lee, Woo-Jin; Kim, Eun-Ah; Woo, Yeong-Jin; Park, Ihho; Yu, Ji-Hun; Ha, Taeho; Choi, Yoon Suk; Lee, Hak-Sung
ABSTRACT: Tungsten carbide (WC) in Ni-based powders is a promising candidate for laser-based additive manufacturing because WC is an extremely hard material, whereas Ni is tough and weldable. However, WC particles that are directly exposed to a laser beam can be degraded or disintegrated into tungsten and carbon as a result of excess energy. In contrast, particles in the melt pool are relatively stable. In this study, the direct energy deposition method was used with irregular and spherical WC particles in metal powder. Irregular WC particles were found to be more directly affected by laser irradiation. To explain the effects of WC particle shapes on direct laser damage, a finitepoint calculation was performed to estimate the sinking time in the melt pool. The rectangular shape particles a longer sinking time depending on the rotation angle, whereas the spherical particles sank uniformly based on the difference in the effective area of resistance.